A Computational Model of Public Support for Insurgency and Terrorism A Prototype for More-General Social-Science Modeling - Davis, Paul K. (RAND Corporation, 2013)
This report builds on earlier RAND research that used qualitative conceptual causal models called "factor trees" to identify the factors that contribute to aspects of terrorism or insurgency and how the factors relate to each other. This report goes beyond the qualitative by specifying a prototype computational social-science model of public support for terrorism and insurgency. The model illustrates designing for reusability and composition.